Answer:
The answer is -77
Step-by-step explanation:
Ok, so assuming by x2 you mean x squared, I will solve this. So basically when you have a function, f(-7) would mean that you would have to replace all the x's in the equation with -7. So let's write that out. that would be f(-7) = -7^2 + (-7*4). So now according to PEMDAS, you would solve the exponent first, and -7^2 is equal to -49, because when you solve it you would do -(7^2), which is -(49), which is then -49. So now you have f(-7)= -49+ (4*-7). Solving for (4*-7), you get -28. This leaves you with -49 + (-28), which is -49 - 28. Simplifying that, you get the answer, which is -77.
Answer:
6
Step-by-step explanation:
find a common factor
6*8=48
8*6=48
Here I'll Simplify it to show the work.
You need PEMDAS
9(2*2+4÷2)
9(4+4÷2)
9(8÷2)
9(4)
9(4) = 9 × 4 = 36
The Answer is 36.
Your answer would be option B. 2y² - y - 6 = 0. This is because if you were to substitute x = y² - 1 into the equation 2x - y = 4, you would get 2(y² - 1) - y = 4, which expands into 2y² - 2 - y = 4, and then simplifies to 2y² - y - 6 = 0.
I hope this helps!